Transthyretin Glu54Leu – an unknown mutation within the Swedish population associated with amyloid cardiomyopathy and a unique fibril type. (18th August 2019) - Hellman, Urban; Lång, Kenneth; Ihse, Elisabet; Jonasson, Jenni; Olsson, Malin; Lundgren, Hans-Erik; Pilebro, Björn; Westermark, Per; Wixner, Jonas; Anan, Intissar
Abstract: For the first time, we report of a Swedish family of five individuals with a TTR Glu54Leu (p. Glu74Leu ) mutation in the transthyretin gene. This mutation has been previously described a few times in the literature, but no phenotypic or clinical description has been done before. The most common mutation in the Swedish population is TTRVal30Met and is mostly found in the Northern part of Sweden. Interestingly, the TTRGlu54Leu mutation was found in the same endemic area. The main phenotype of the TTR Glu54Leu patients is severe cardiomyopathy, which resulted in heart transplantation for the index person. As previously seen for ATTR amyloidosis patients with mainly cardiomyopathy, the amyloid fibrils consisted of a mixture of full-length and fragmented TTR species. However, western blot analyses detected a previously unrecognized band, indicating that these patients may have a third, so far unrecognized, fibril composition type that is distinct from the usual type A band pattern.